Thaúmata : Critical and Underrepresented Perspectives on Hagiography and Hagiographic Studies - Boada-Benito, Aitor, (Numen Book Series., 2025)
Thaúmata: Critical and Underrepresented Perspectives on Hagiographic Studies gathers renowned international scholars to reflect and explore the study of Hagiography and its sources. Breaking through chronological and spatial boundaries, this compelling volume critically examines sanctity, holy figures, and the study of them across diverse cultures, periods, and sources. Offering fresh insights and innovative methodologies while acknowledging the most established perspectives, Thaúmata broadens our understanding of holiness in history, making it an indispensable resource for academics in Religious Studies and related fields.